The end of prisons : reflections from the decarceration movement - Nagel, Mechthild.; Nocella, Anthony J. (Value Inquiry Book Series, 2013)
This book brings together a collection of social justice scholars and activists who take Foucault's concept of discipline and punishment to explain how prisons are constructed in society from nursing homes to zoos. This book expands the concept of prison to include any institution that dominates, oppresses, and controls. Criminologists and others, who have been concerned with reforming or dismantling the criminal justice system, have mostly avoided to look at larger carceral structures in society. In this book, for example, scholars and activists question the way patriarchy has incapacitated women and imagine the deinstitutionalization of people with disabilities. In a time when popular sentiment critiques the dominant role of the elites (the "one percenters"), the state's role in policing dissenting voices, school children, LGBTQ persons, people of color, and American Indian Nations, needs to be investigated. A prison, as defined in this book, is an institution or system that oppresses and does not allow freedom for a particular group. Within this definition, we include the imprisonment of nonhuman animals and plants, which are too often overlooked.